Pengaruh Struktur Aset, Market Value Added (MVA), Debt To Equit Ratio (DER), Serta Earning Per Share (EPS), Terhadap Harga Saham Pada Perusahaan Properti Yang Terdaftar Di Bursa Efek Indonesia (BEI) Pada Tahun 2017 – 2021 - Vallen Aprilia Tehja; Angeline Yangness; Wirda Lilia; Wenny Anggeresia Ginting (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to determine the effect of Asset Structure, Market Value Added (MVA), Debt to Equity Ratio (DER), and Earning Per Share (EPS), on Stock Prices in Property Companies Listed on the Indonesia Stock Exchange (IDX) in 2017 - 2021. This study uses quantitative data types and the research population to be used in the study are property companies listed on the Indonesian stock exchange (bei) in 2017 - 2021 as many as 32 companies with a research sample of 160 samples. The results of the study partially show that Asset Structure has an influence on Stock Price by having a tcount value (0.208) > ttable (1.97529) with a significant level of 0.033 <0.05, Market Value Added has an influence on Stock Price by having a tcount value (5. 877) > t table (1.97529), Debt to Equity Ratio has no effect on Stock Price by having tcount (0.217) < t table (1.97529) with a significant level of 0.828 < 0.05, Earning Per Share has an influence on Stock Price by having tcount (4. 757) > ttable (1.97529) with a significant level of 0.000 < 0.05 and Asset Structure, Market Value Added, Debt to Equity Ratio and Earnings Per Share have an effect and significant on Stock Prices by having Fcount (5.527) > Ftable (2.43) with a significance of 0.000 < 0.05. Keywords: Asset Structure, Market Value Added, Debt to Equity Ratio, Earning Per Share (EPS) and Stock Price.